The effects of Teen Clubs on retention in HIV care among adolescents in Windhoek, Namibia - Farai K. Munyayi; Brian van Wyk (AOSIS, 2020)
Background: Adolescents living with HIV (ALHIV) are notably underserved by the national HIV programmes globally because of their unique needs. Of particular concern is limited access to and availability of adolescent-friendly antiretroviral therapy (ART) services, which contribute to poor retention in care in many sub-Saharan African countries. A Teen Club intervention was introduced in 2010 in Windhoek, Namibia, to improve retention in care among ALHIV through psychosocial support in a peer-group environment. Objectives: To compare the effects of the Teen Club intervention against standard care on retention in HIV care amongst adolescents at a Paediatric ART clinic. Method: A retrospective cohort analysis of adolescents aged 10-19 years receiving ART between July 2015 and June 2017 was conducted. Routine patient data were extracted from an electronic database and patient registers. A sample of 385 participants was analysed: 78 in the Teen Club and 307 in standard care. Retention was measured by assessing attendance to prescribed clinic visits up to 24 months. Comparisons were assessed with the Chi-square test, and Kaplan-Meier survival analysis was conducted to analyse differences in retention rates. Results: The overall retention rate at 24 months among all adolescents was 90.1%, with no statistically significant difference between those in Teen Club (91%) and those in standard care (89%) (p = 0.956). Younger adolescents (10-14 years) had better retention rates at 24 months compared to older adolescents (15-19 years) (94% vs. 86%; p = 0.016). Retention rates were significantly higher for adolescents on first-line ART regimen (vs. second line: hazard ratio [HR] = 0.333; 95% confidence interval [CI] = 0.125-0.889); on ART ≥ 12 months (vs. 12 months: HR =0.988; 95% CI = 0.977-0.999); and those to whom their HIV status was disclosed (HR = 0.131; 95% CI = 0.025-0.686). Conclusion: Group-based adherence support interventions did not improve retention rates for younger adolescents in specialised paediatric ART clinics but may still hold the potential for improving retention rates of older adolescents.